The Model T and a Peek Behind the Curtain? - Wroten, Chris (Canadian Journal of Optometry, 2018)
Change. The Future. Two similar, but complicated, concepts that many of us either fear due to uncertainty, or aggressively seek out due to the thrill of being on the cutting edge. If we’re paralyzed by uncertainty, it’s easy to get left behind as new and better opportunities emerge. On the flip side, it’s easy to get burned by constantly [...]